Enhancing standards management capabilities of the OECS countries : final report - Rhynd, Dudley B. ([CARICOM Secretariat] [Georgetown]GY, 2001)
Presents the key findings and recommendations which emerged out of the work done during the CARICOM Secretariat/Caribbean Development Bank Project. Looks at cooperation and efficiency in the area of standards management in light of financial constraints and limited resources throughout countries of the OECS. Deals with the implementation of internationally accepted quality standards including ISO 9000 series on Quality Management Systems and the ISO 1400 series on Quality Management Systems.